Letter - Stevenson, Daniel M., Sir
042-0122-001 Telegrams: "Ambulance, Cleveden, Glasgow" Telephone: West 2470 Secretary: Miss R. RIFFKIN Scottish Ambulance Unit in Spain 5 CLEVEDEN ROAD, GLASGOW, W.2, 9th August, 1937. Chairman: Sir Daniel Stevenson. Bart.. LL.D. Committee: Ishbel, Marchioness of Aberdeen and Temair, G.B.E. The Countess of Oxford and Asquith. Sir Henry Ballantyne William Black. Esq. Bailie Elger. A. Forrester-Paton, Esq. The Hon. Mrs. Forrester-Paton. Professor and Mrs. Glaister. Sir Thomas and Lady Glen-Coats. Mrs. John M. Hogg, Lenzie. Miss Jacobsen. Sir John Mann, K.B.E. Sir David Mason, LL.D. David Perry, Esq. Sir Andrew H. Pettigrew, LL.D. Ralph Risk, Esq., M.C. The Rt. Hon. Sir Archibald Sinclair, Bart. M.P. Lady Swan. Professor Walton. Lady Wilson, of Uddingston. In affiliation with The National Joint Committee for Spanish Relief, Chairman: The Duchess of Atholl, M.P. Vice-Chairmen: The Earl of Listowel Miss Eleanor Rathbone, M.P. Hon Secretaries: Mr. D.R. Grenfell, M.P. Capt. J.R.J. Macnamara, M.P. Mr. Wilfrid Roberts, M.P. Treasurer (pro tem.): Mr. Wilfrid Roberts, M.P. Dear Sir Walter, I duly received your kind letter of 30th July the terms of which I very much appreciated. In your last paragraph you say you will always be glad to hear from time to time of the progress of the Unit. The members are now here and all of them, particularly Miss Jacobsen, are eager to return. The whole situation has been discussed by the Committee which, although of the opinion that they have "done their bit" has consented and we hope to see them off in about a fortnight. Miss Jacobsen has a few visits to pay in London and would particularly like to give you a first-hand account of the work. If you would kindly let me know what hour on Friday, Saturday or Sunday (Saturday or Sunday, if possible) would suit you best, she would arrange her other calls to fit in. Yours sincerely, D.M. Stevenson Sir Walter Citrine, K.B.E. Transport House Smith Square London, S.W.1. 292/946/42/122